2019
DOI: 10.3390/en12081549
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Efficiency and Material Properties of Friction Stir Channelling Applied to Aluminium Alloy AA5083

Abstract: The Friction Stir Channelling (FSC) is a novel advanced solution for producing internal closed channels along any desired path with a constant or continuously modified shape along the path in a single manufacturing step. The channels are formed by continuous extraction of part of the stirred processed material into external flash. In this work, the performance of channels with the same shape and dimensions but produced by FSC and milling respectively, are compared using an experimental calorimeter setup with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…In friction stir-based channeling, each wall of the channel is resulted with unique and distinct surface roughness features. [62,57,66,70,77] Figure 23 shows differences in surface roughness within channel's walls. [57,70,77] These differences in surface roughness are greatly influenced by the processing characteristics of friction stir-based channeling.…”
Section: Surface Features and Performancementioning
confidence: 99%
See 3 more Smart Citations
“…In friction stir-based channeling, each wall of the channel is resulted with unique and distinct surface roughness features. [62,57,66,70,77] Figure 23 shows differences in surface roughness within channel's walls. [57,70,77] These differences in surface roughness are greatly influenced by the processing characteristics of friction stir-based channeling.…”
Section: Surface Features and Performancementioning
confidence: 99%
“…[51] Figure 23. Surface features of channel manufactured by friction stir channeling (a-d) cross-section of channel with four different sides, [77] (e) X-ray microcomputed tomography of channel, [70] (f) Channel surfaces and its confocal laser scanning microscopy for channel. [57] channel is resulted from deposited material where higher surface roughness is obtained.…”
Section: Surface Features and Performancementioning
confidence: 99%
See 2 more Smart Citations
“…They have also found that the influence of the tool shoulder on the channel formation increases along with the channel length. Channels produced by FSC and tested by Karvinen et al [9] were able to withstand an internal pressure up to 380 bar and results using air as cooling media showed that the FSC enhanced the heat transfer by about 45 % compared with smoother milled channels. A recent addition to these techniques is the Hybrid Channelling (HC), which enables simultaneous welding and channelling, in one action, of multiple metal components from similar or dissimilar materials and geometries.…”
Section: Introductionmentioning
confidence: 99%